Management of pregnancy in cystic fibrosis. Issue 2 (7th June 2022) - Montemayor, Kristina; Tullis, Elizabeth; Jain, Raksha; Taylor-Cousar, Jennifer L.
With recent therapeutic advances in care, people with cystic fibrosis (CF) are living longer and healthier lives. Development of the cystic fibrosis transmembrane conductance regulator (CFTR) modulator therapies has led to improved function of the CFTR protein resulting in improved lung function, decreased rates of pulmonary exacerbations and improved nutritional status for the majority of people with CF. Given improved quality and quantity of life, more people with CF are considering becoming pregnant than ever before. Since the first reported pregnancy in a woman with CF in 1960, the management of pregnancy in CF has been of increased interest and is an active field of research. In this review, we aim to discuss the management of pregnancy in CF. We discuss the optimisation of preconception health, management of maintenance CF therapies, and use of CFTR modulators during pregnancy and lactation. We also describe the management of pulmonary exacerbations during pregnancy as well as the unique management of pregnancy in a post-transplant patient with CF. Educational aims: To describe considerations for optimisation of preconception health. To describe the management of chronic CF therapies including CFTR modulators during pregnancy and lactation. To describe treatment of an acute pulmonary exacerbation during pregnancy. To describe the management of pregnancy in individuals with CF following organ transplantation. With recent therapeutic advances in care, more people with CF are pursuing pregnancy. Managing pregnancy in CF focuses on preconception health with judicious use of chronic maintenance therapies and CFTR modulators throughout pregnancy and lactation. https://bit.ly/3qLDSNa